(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the IoT, things are expected to become active participants where they are able to interact and communicate among themselves by exchanging data and information sensed about the environment. For that they react autonomously to the real world events and provide services with or without direct human intervention. In this paper we use IOT for energy efficient Environmental Conditions sensing and controlling in Home.In this paper we will see how to provide fully smart environment condition monitoring by various sensors (Temperature, Humidity, Light and Level) for providing necessary data to automatically adjust the comfort level in homes by optimize use of energy. We also use prediction here for automatically detection and resolution of any problem in the devices. For that we are using Naïve Bayes Classifier algorithm for data mining. It will send email or SMS to required technician for service and it will also notify the owner. This gives a huge advantage on the smart home systems using IoT.